2014
DOI: 10.1590/1517-3151.0196
|View full text |Cite
|
Sign up to set email alerts
|

Digital controller design considering hardware constraints: application in a paraplegic patient

Abstract: Introduction: A methodology was developed for implementing closed-loop control algorithms and for evaluating the behavior of a system, considering certain component restrictions used in laboratory implementation. Methods:Mathematical functions representing a model of the biological system were used for knee extension/fl exion movements. A Proportional Integral Derivative (PID) controller and another one using the root locus method were designed to control a patient's leg position by applying functional electri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 12 publications
(26 reference statements)
0
10
0
Order By: Relevance
“…In [39] and [40], are considered only constant reference signals and all set of the desired operation points for obtaining the maximum and minimum values of the plant nonlinear functions, to get the local models following the method proposed in [30]. The proposed method can be implemented the same as [50] and [51]. By the authors knowledge, in [50], the Takagi-Sugeno fuzzy models method to control the knee joint of paraplegic patients was implemented for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…In [39] and [40], are considered only constant reference signals and all set of the desired operation points for obtaining the maximum and minimum values of the plant nonlinear functions, to get the local models following the method proposed in [30]. The proposed method can be implemented the same as [50] and [51]. By the authors knowledge, in [50], the Takagi-Sugeno fuzzy models method to control the knee joint of paraplegic patients was implemented for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, the oscillation was eliminated from the pulse width curve, stabilizing in values of very close to one another in both simulations. As mentioned by Sanches et al in [8] "An electric current with a balanced, biphasic, rectangular waveform with a pulse width of 220 s was applied to the skin surface of the volunteer. The signal amplitude was then held constant for 3 seconds and considered a "step pattern" [5].…”
Section: Discussionmentioning
confidence: 99%
“…When electrical stimulation is applied to the quadriceps of a patient, using the controller, the knee joint angle can be varied from 0 ∘ to 30 ∘ . The authors considered the leg mathematical model proposed by [5], and they showed that, for the conditions considered in their experiments, a simple one-pole transfer function was able to model the relationship between stimulus pulse width and active muscle torque [8].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the discrete T-S fuzzy model is obtained, using local models (24) and the membership functions (23):…”
Section: Nonlinear Dynamic Model Of the Leg Of The Paraplegic Patimentioning
confidence: 99%
“…In [18] and subsequent articles [19]- [22], and [23] published by our research group, some theories are employed to control knee joint movement using neuromuscular electrical stimulation. In [24], an article was published describing control application in paraplegic patients.…”
Section: Introductionmentioning
confidence: 99%